Existence of positive solutions for third-order semipositone boundary value problems on time scales - Zhang, Xinguang; Tian, Hui; Wu, Yonghong; Wiwatanapataphee, Benchawan (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we consider the existence of positive solutions for a semipositone third-order nonlinear ordinary differential equation on time scales. In suitable growth conditions, by considering the properties on time scales and establishing a special cone, some new results on the existence of positive solutions are established when the nonlinearity is semipositone.